Processing and nanoclay induced piezoelectricity in poly(vinylidene fluoride-co-hexafluoro propylene) nanohybrid for device application. (5th August 2016) - Gaur, Anupama; Shukla, Rahul; Kumar, Brajesh; Pal, Arkadeb; Chatterji, Sandeep; Ranjan, Rajeev; Maiti, Pralay
Abstract: Process and nanoparticle induced piezoelectric super toughened poly(vinylidene fluoride-co-hexafluoro propylene) (HFP) nanohybrids have been developed for device application. The nanohybrids have been prepared by incorporating organically modified nanoclay through solution route. The nanohybrids show improvement in toughness and modulus along with piezoelectric phases compared to pure HFP. Piezoelectric phase has further enhanced to 75% in nanohybrid after uniaxial stretching of the thin film at moderately high temperature as compared to meager 18% β-phase before stretching. The structural changes including quantitative measurements have been confirmed through X-ray diffraction, spectroscopic and thermal studies. The structural and morphological origins of super toughening phenomena have been worked out. The piezoelectric and pyroelectric coefficients (d33 and p) exhibit significant increase after stretching at high temperature and the relative improvements are more in nanohybrid than that of pure HFP, arising from the presence of greater amount of β-phase in nanohybrid. The effect of structure on ferroelectricity has been studied through polarization-electric field hysteresis loop confirming greater maximum polarization, remnant polarization and coercive field for nanohybrid against pure HFP. Finally, fabrication of the unimorph has been performed using the high piezoelectric coefficient materials. The greater voltage generation under impulse load is demonstrated for nanohybrid along with longer time response vis-à-vis pure HFP clearly indicating the superior piezoelectric device made using nanohybrid where the extent of piezoelectric phase is considerably higher. Graphical abstract: Higher piezoelectricity in polymer nanohybrid has been developed through processing with greater device efficiency. Highlights: Nanohybrid of poly(VDF-co-HFP) and organically modified clay has been prepared for device fabrication with greater efficiency. Piezo- and pyroelectric studies have reported using nanohybrid. Better device performance using nanohybrid as compared to pure polymer in similar condition due to greater piezoelectric phase in presence of nanoclay.